Escherichia fergusonii bacteremia after esophagectomy: a case report and literature review - Jiang, Yu-Yang; Zhang, Yi; Hu, Yang; Guo, Yuan (Journal of international medical research, 2023)
We report the case of a 68-year-old man who experienced Escherichia fergusonii bacteremia after esophageal cancer surgery. The patient presented with complaints of abdominal pain persisting for 1 week. The patient was diagnosed with esophageal malignancy, which was confirmed by surgical exploration and pathological biopsy. The patient developed septic shock on postoperative day 12, and blood culture suggested the growth of E. fergusonii. After treatment with meropenem, the patient’s clinical symptoms improved significantly, and the second culture was negative. In this paper, we discuss the characteristics, diagnosis, and treatment of E. fergusonii. E. fergusonii is rarely reported, and its pathogenesis, drug resistance, and potential effects have not been completely confirmed. Thus, this case report adds valuable knowledge to the literature on E. fergusonii.